Characterizations of LiCaAlF6:Eu2+ ceramics as neutron scintillator: Primitive experimental studies and future prospective. (November 2017) - Okada, Go; Fukuda, Kentaro; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: We have synthesized Eu-doped LiCaAlF6 ceramics by using a spark plasma sintering (SPS) technique and then characterized for neutron scintillator applications. Despite the difficulties to fabricate fluoride compounds in a ceramic form, we have successfully obtained solid bulk LiCaAlF6 ceramics by the SPS. However, the sample significantly tanned dark brown with increasing the sintering temperature. All the samples emit in the near UV range due to the d-f transitions of Eu 2+ ion by both photoluminescence (PL) and radioluminescence (RL), and the lifetimes were reasonably consistent in the range of 1.5–1.8 μs (PL) and 1.4–1.9 μs (RL). Among the ceramic samples tested, the one sintered at the lowest temperature showed the highest scintillation light yield (7600 ph/n) which is smaller than that of single crystal scintillator by a factor of approximately 4. Nevertheless, the energy transportation efficiency was estimated to be higher in some of the ceramic samples. It was also revealed that the latter efficiency was complementarily related with the thermally stimulated luminescence of corresponding ceramics. Highlights: LiCaAlF6 :Eu 2+ ceramics were synthesized by SPS. LiCaAlF6 :Eu 2+ ceramics were characterized for neutron scintillator. The sample sintered at 400 °C showed the highest light yield of 7600 ph/n. The light yield and TSL response were complementarily related.